Does the Source of Nitrogen Affect the Response of Tomato Plants to Saline Stress? - and Samira Aschi-Smiti, Faouzi Horchani*, Olfa R’bia, Rim Hajr (Current Botany, 2011)
The aim of the present study was to investigate the effects of the source of nitrogen (N) nutrition on the response of tomato (Solanum lycopersicum L. cv. Rio Grande) plants to saline stress (100 mM NaCl). To this end, plant growth, chlorophyll and carbohydrate levels, ion contents as well as N compounds and main N-metabolizing enzymes (nitrate reductase and glutamine synthetase) were analyzed in salt-treated and control plants grown in the presence of either NO3-, NH4+, or the mixture of NO3- and NH4+. Our results showed that plant growth declined under saline stress but NO3--fed plants were less sensitive to salinity than NH4+-fed plants. This different sensitivity was due mainly to a better maintenance of root growth and root nitrate reductase activity in NO3--fed plants. Concomitantly, leaf chlorophyll content was significantly decreased, regardless of the N source. Salinity affects the uptake of several nutrients in a different way, depending on the N source. Thus, sodium was accumulated mainly in NH4+-fed plants, especially in roots, displacing other cations such as NH4+and potassium. It is concluded that the N source is a major factor affecting tomato responses to saline stress, plants being more sensitive when NH4+ is the source used. The different sensitivity is discussed in terms of a competition for energy between N assimilation and sodium exclusion processes.